Keberlakuan Hukum Penodaan Agama di Indonesia Antara Tertib Hukum dan Tantangan Hak Asasi Manusia - Heru Susetyo; Farida Prihatini; Abdurakhman; Nurindah Hilimi; Intan Mahabah; Ira Apriyanti; Suri Rahmadhani (Faculty of Law Hang Tuah University, 2020)
Indonesia with its five pillars of Pancasila binds the State and its citizens to